1965
DOI: 10.1002/pen.760050312
|View full text |Cite
|
Sign up to set email alerts
|

The deterioration of polypropylene by oxidative degradation

Abstract: 90--0 a 120oc "6 loo--L 80--70--14OOC 0 0" m 60--

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1968
1968
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…The variation of S O2 now enables to simulate the whole range of induction times compiled from the literature under 0.1 MPa and 0.02 MPa, except the lowest values attributed to polypropylenes which are atactic, preoxidized or with a high catalyst residues amount (Figure ). The slope of the Arrhenius graph, i.e.…”
Section: Discussion: Towards a “Universal” Kinetic Modelmentioning
confidence: 99%
“…The variation of S O2 now enables to simulate the whole range of induction times compiled from the literature under 0.1 MPa and 0.02 MPa, except the lowest values attributed to polypropylenes which are atactic, preoxidized or with a high catalyst residues amount (Figure ). The slope of the Arrhenius graph, i.e.…”
Section: Discussion: Towards a “Universal” Kinetic Modelmentioning
confidence: 99%
“…Normally polymers are applied below their processing temperature, it has been shown that at these temperatures in an environment without oxygen polymers hardly degrade [1,2,3]. The reduction of the properties in an air environment is a result of reactions with oxygen.…”
Section: Influence Of Oxygenmentioning
confidence: 99%
“…Another decomposition reaction of hydroperoxides with lower activation energy is the decomposition catalyzed by transition metal ions [40,41] Termination reactions are bimolecular (stage 4). In the presence of sufficient air, which normally is the case during long-term degradation of polymers, only the reaction of two peroxy radicals has to be considered [1]. The reaction depends on the type of peroxy radical present.…”
Section: Influence Of Oxygenmentioning
confidence: 99%
“…It is known that the core of crystallites is inert to oxidation, but their surfaces and boundary regions could well be oxidized (e.g., scission of the tie-chains between the crystallites). 17 On the basis of the results, it is suggested that the decrease in melting peak temperature is due to less-ordered crystallites in aged material (i.e., an oxidation-induced increase in surface energy of the crystallites). Figure 4 presents profiles through thickness of the relative carbonyl ratio as a function of distance from surface for heat-stabilized samples (S2).…”
mentioning
confidence: 96%